Literatur Review: Hak dan Kewajiban Pasien, Keluarga Masyarkat dan Tenaga Medis dalam Pelayanan Kesehatan Bencana - Jaury Douglas Pardomuan; Handoyo Prasetyo (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Health services are a critical aspect that requires coordination and cooperation from various parties, including patients, families, communities and medical personnel. Therefore, this research aims to analyze the rights and obligations of patients, families, communities and medical personnel in disaster health services. The method used is literature study. Google and Google Schoolar are used as the main sources of the database used from 2020 to 2024 to extract research via publish or perish software. From the research that has been conducted, disaster health services are a very complex and challenging aspect of the health system, which requires a multi-disciplinary and collaborative approach. A deep understanding of the rights and obligations of patients, families, communities and medical personnel is a strong basis for building a health care system that is fair, effective and sustainable. Cooperation between governments, international organizations, non-governmental organizations, local communities and individuals is essential to ensure that disaster response and recovery efforts can be carried out in a coordinated and effective manner. The development of supportive policies and regulations, as well as adequate funding, are also critical to strengthening disaster health services.